Electrospun Sandwich‐Structure Composite Membranes for Wound Dressing Scaffolds with High Antioxidant and Antibacterial Activity. Issue 2 (6th December 2017) - Li, Jinzhen; Hu, Yang; He, Ting; Huang, Mengwen; Zhang, Xiangchao; Yuan, Jinying; Wei, Yen; Dong, Xianming; Liu, Wei; Ko, Frank; Zhou, Wuyi
Abstract: In this study, the sandwich‐structured composite (SSC) membranes with well‐antibacterial and antioxidant properties, which have the promising application as wound dressing, are successfully fabricated by combining an electrospinning process. The SSC membranes are composed of three layers, including the bottom polyvinylidene fluoride fibrous layer, the middle curcumin/polylactic acid (PLA) microsphere layer, and the top enrofloxacin/PLA fibrous layer, respectively. The obtained SSC membranes are characterized in terms of morphology, component, and mechanical property using scanning electronic microscope, X‐ray diffractometer, Fourier transform infrared spectroscopy, and universal electronic testing machine, respectively. Moreover, in vitro drug release, antioxidant activity, antimicrobial activity, and biocompatibility of the SSC membranes are also evaluated. The results showed that the obtained composite membranes indeed possess the sandwich structure, where the middle microsphere layer is located between two fibrous surface layers. It is found that the drug‐loaded SSC membranes show excellent antioxidant activity against OH and DPPH free radicals and antibacterial activity against Staphylococcus aureus, Escherichia coli, Streptococcus pneumoniae, Pseudomonas aeruginosa, and Candida albicans . The combination of electrospinning and electrospraying opens up a new way to fabricate a variety of composite membranes with a sandwich structure, which have promising potential application as wound dressing scaffolds. Abstract : Sandwich‐structured composite (SSC) membranes are successfully fabricated by combining an electrospinning process. The prepared SSC membranes show a hydrophobic surface and a hydrophilic surface, and possess well antibacterial and antioxidant properties. This study demonstrates an innovative strategy for creating SSC membranes, which have promising application prospects as wound dressings.